Sistem Pendukung Keputusan Rekomendasi Pemilihan Smartphone Menggunakan Metode Simple Additive Weighting (SAW) - Syahputra, Adhe Rifqi; Ritonga, Alven Safik (Faculty of Engineering, Wijaya Putra University, 2023)
Smartphones are the latest technology from ordinary cellphones which are in great demand because with current technological advances many people need smartphones for their daily needs such as work, education and others. Many buyers are confused about which smartphone to buy because of the many brands and types of smartphones being marketed. This research aims to produce recommendations as well as Smartphones to buyers. Decision Support System (SPK) uses the Simple Additive Weighting (SAW) method. This Smartphone Selection Decision Support System is implemented in the form of a web. In this system, users can input smartphone criteria that suit their needs with the Smartphone Recommendation Support System making it easier for buyers to buy smartphones according to their needs.